Fluorimetric and HPLC-based dengue virus protease assays using a FRET substrate - Nitsche, Christoph; Klein, Christian D. (Antiviral methods and protocols, 2013)
The number of dengue virus infections is increasing and the dengue NS2B-NS3 protease is considered a promising target for the development of antiviral therapies. Therefore, reliable and fast screening systems are needed for the discovery of new lead structures. In this chapter, we describe two dengue virus protease assays based on an internally quenched, high-affinity Förster resonance energy transfer (FRET) substrate (K m = 105 μM). A fluorimetric assay using a microtiter fluorescence plate reader can be used for high-throughput screening of a large number of compounds. Alternatively, an HPLC-based assay with fluorescence detection can be applied to confirm the compound hits and to avoid false-positive results that may arise due to the inner filter effect of some compounds.